Comparative Study on Compositions and Functional Properties of Porcine, Chicken and Duck Blood - Supaluk Sorapukdee; Supawadee Narunatsopanon (My University, 2017)
Hematological, chemical and functional characteristics of porcine, chicken and duck blood were evaluated. A porcine blood sample showed the most abundant red blood cell, hemoglobin concentration, packed cell volume and plasma protein content as well as its freeze-dried blood possessed the highest contents of protein, fat, Cu and Cr with the highest percentage of heme iron (
Keywords: Protein Hydrolysis and Bioactive Peptides